Novel Correlations among the Histopathological Components of Oral Squamous Cell Carcinoma - Ablahad, Aween Auda; Mousa, Hashim Dawood; Jalal, Jalal Ali (Open Access Macedonian Journal of Medical Sciences, 2022)
Background: Oral squamous cell carcinoma (OSCC) is an aggressive tumor with high mortality and morbidity rates. Aims:In this study, we aimed to probe whether there is association between stromal histopathological parameters with patient data, as well as, the correlation of these parameters with each other. MaterialsandMethods:This study was performed at University of Duhok, College of Dentistry, the practical section was carried out between February 2022 and June 2022 as follow:A group of 86 formalin fixed paraffin embedded (FFPE) samples of OSCC and 20 FFPE samplesof healthy gingiva were stained with Hematoxylin and eosin(H&E) and Mason’s trichrome (MT)stains. Tumor/ stroma ratio(TSR), stromal tumor-infiltrating lymphocytes(sTIL), budding activity (BA), cell nest size (CNS), orientation and packing of collagen fibers and collagen fibercontent(CFC) were evaluated. These histomorphological parameters were correlated with clinicopathological characteristics and with each other. Statistical Analysis Used: Chi square test, fisher exacts test and spearman’s rank correlation coefficient were used for analyzing our study data. Results: Tumor/ stroma ratio, BA, CNS, orientation and packing of collagen fibers, and CFC were significantly associated with pT stage of the tumor. Moreover, significant correlations were observed among TSR, BA, CNS and CFC. In addition, orientation and packing of collagen fibers were significantly correlated with each other. Conclusions: Novel correlations were found between collagen fiber features with TSR, BA, and CNS in an easy and cost- effective methods.